Implementasi Sistem Informasi Pelayanan Administrasi Berbasis Web sebagai Upaya Peningkatan Kualitas Pelayanan Publik di Kantor Wali Nagari IV Koto Mudiek - Yaslinda Lizar; Muhammad Nizam (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2026)
Digital transformation in village government has become an important strategy to improve the effectiveness, efficiency, and transparency of public services. The IV Koto Mudiek Village Office experienced several administrative service challenges because population data management and document processing were still conducted manually. These conditions resulted in repetitive data entry, slow service delivery, difficulties in document archiving, and a high risk of administrative errors. This community service program aimed to improve administrative services through the implementation of a web-based Administrative Service Information System accompanied by technical assistance for village officials. The implementation stages included needs assessment, system development, application deployment, data migration, user training, and system evaluation. The results demonstrated that the system successfully supported population management, birth registration, death registration, migration administration, and automatic generation of administrative documents. Furthermore, the implementation accelerated administrative services, improved data accuracy, simplified report generation, and enhanced the digital competencies of village officials. Overall, the program contributed significantly to strengthening digital public services at the village government level.